Silicene/ZnI2 van der Waals heterostructure: tunable structural and electronic properties. (7th May 2021) - Hassan, Md. Sakib; Islam, Md. Sherajul; Park, Jeongwon
Abstract: By utilizing ab initio density functional theory, the structural and electronic properties of novel silicene/ZnI2 heterobilayers (HBLs) were investigated. Constructing HBLs with ZnI2 in different stacking configurations leads to direct bandgap opening of silicene at K point, which ranges from 138.2 to 201.2 meV. By analyzing the projected density of states and charge density distribution, we found that the predicted HBLs conserve the electronic properties of silicene and ZnI2 can serve as a decent substrate. The tunability of electronic properties can be achieved by enforcing biaxial strain and by varying interlayer distance where bandgap can get as low as zero to as high as 318.8 meV and 290.7 meV, respectively depending on the stacking patterns. Maintenance of the remarkable features of silicene, high mobility of charge carriers, and fine-tuning of bandgap pave the way to construct new nanoelectronic devices using these novel silicene/ZnI2 HBLs.